Estimação de parâmetros para modelos de escoamento multifásico sob incertezas - Monteiro, Danielle de Oliveira (2018)
Although very common in the oil industry, uncertainty modeling is not widely used in the production stage including the multiphase elevation and flow area. The multiphase flow models present several sources of uncertainty, such as their own modeling originated by the use of flow correlations, in addition to the uncertainties in the values of the variables used in the model construction. For these reasons, a methodology is proposed that, in a manner analogous to the Reservoir Engineering process, performs the adjustment of the multiphase flow models considering a history of production tests and their associated uncertainties, with the objective of minimizing the discrepancy between the simulated data and observed data. The first stage of the work consists in quantifying the uncertainties present in the production variables through a statistical treatment of the production data. The second step involves the construction of the adjustment model. As a result it is expected an automatic adjustment model of multiphase flow models that takes into account a history of production tests and the uncertainties associated with production variables.